Family as a space of development of child’s social skills - Piecuch, Ewelina (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
According to developmental psychology childhood is the time when the child develops, both the personality as well as the whole body. All the factors influencing the child from the very begining have a fundamental meaning for the shaping of the young human. All the deficiencies that a child experiences during early childhood have great repercussions in the later stages of development of their life. Emotional deficiencies cause disorders in this field. Excessive care can also bring serious consequences. The most important role in this process is played by the child’s parents (caregivers), closely and distantly related family environment, peers, educational institutions supporting parents in upbringing along with teachers. The way in which education is achieved decides the whole existence of the young human.
Keywords: family; child; childchood; social skills; development; development of social skills